Correction: Kemerink-Seyoum, J.S.; et al. Title Attention to Sociotechnical Tinkering with Irrigation Infrastructure as aWay to Rethink Water Governance. Water 2019, 11, 1670 - Kemerink-Seyoum, Jeltsje Sanne; Chitata, Tavengwa; Guzmán, Carolina Domínguez; Sanchez, Luis Miguel Silva-Novoa; Zwarteveen, Margreet Z. (MDPI AG, 2021)
The authors wish to make the following correction to this paper [1]: The author name “Luis Miguel Novoa-Sanchez” should be “Luis Miguel Silva-Novoa Sanchez”. There is one inaccuracy in this article [1]. The fifth sentence in the second paragraph on page 4, “Sociotechnical tinkering helps not only to reveal : : : , but it also provides a chance to a priori define and decide where or what agency is, or where : : : ” should be “Sociotechnical tinkering helps not only to reveal : : : , but it also provides a chance to study where or what agency is, or where : : : ”. The authors would like to apologize for any inconvenience caused to the readers by these changes.